2021
DOI: 10.1111/iju.14521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intracorporeal urinary diversion on the incidence of benign ureteroenteric stricture after cystectomy

Abstract: Abbreviations & Acronyms BMI = body mass index ECUD = extracorporeal urinary diversion HR = hazard ratio ICG = indocyanine green ICUD = intracorporeal urinary diversion IQR = interquartile range ORC = open radical cystectomy RARC = robot-assisted radical cystectomy RC = radical cystectomy STROBE = Strengthening the Reporting of Observational Studies in Epidemiology Ta = non-invasive papillary carcinoma Tis = carcinoma in situ UES = ureteroenteric stricture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Among five available studies comparing UES rates between RARC and ORC [15,16,[18][19][20][21]23], four showed that RARC promoted higher UES incidence rates compared to ORC, whereas one showed that RARC had lower rates of UES [20]. Moreover, two studies concluded that RARC had a significantly higher UES rates compared to ORC [18,21].…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…Among five available studies comparing UES rates between RARC and ORC [15,16,[18][19][20][21]23], four showed that RARC promoted higher UES incidence rates compared to ORC, whereas one showed that RARC had lower rates of UES [20]. Moreover, two studies concluded that RARC had a significantly higher UES rates compared to ORC [18,21].…”
Section: Incidencementioning
confidence: 99%
“…A benign UES is a known complication of radical cystectomy (RC) and urinary diversion with an incidence rate ranging from 3% to 10% [10][11][12][13][14]. Accumulating evidence from studies focusing on UES has suggested that 6.5%-25.3% of patients who undergo RARC develop UES [15][16][17][18][19][20][21] (Table 1). However, the duration of follow-up and definition of UES in the previous literature vary.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…In the extracorporeal group the UES incidence was 9.6% versus 2.6% in the intracorporeal group. Due to the small sample size and the skewed distribution significance was not reached [21–23,24,25 ▪▪ ]. Reesink et al compared open RC with RARC and ICUD.…”
Section: Urinary Obstructionmentioning
confidence: 99%
“…In the extracorporeal group the UES incidence was 9.6% versus 2.6% in the intracorporeal group. Due to the small sample size and the skewed distribution significance was not reached [21][22][23]24 There was a peak incidence in the year the robot procedure was introduced indicating a learning curve [26 ]. It is thought that manipulation of the ureter, ureteral ischemia, urinary tract infection and ureteroenteric anastomotic urine leakage are risk factors for developing UES [22][23][24].…”
Section: Andandmentioning
confidence: 99%